دراسة عوامل الخطورة عند مرضى الاحتشاءات الفجوية - سعيد هالة; الحتيتي أكرم (Latakia University Journal -Medical Sciences Series, 2018)
الهدف : الاحتشاءات الفجوية نمط من النشبات الدماغية تمتلك مظاهر سريرية و إمراضية فريدة ، و لكن عوامل الخطورة لهذه الاحتشاءات نادراً ما تكون مدروسة .لذلك قمنا بدراسة 65 مريض لديهم احتشاءات فجوية في قسم الأمراض العصبية في مشفى تشرين الجامعي في اللاذقية و 65 شاهد في الفترة الممتدة بين أيار 2017 حتى أيار 2018 . الطرائق :لقد حصلنا على عوامل الخطورة عند المرضى بواسطة استبيان منظم وقمنا بتسجيل العمر ، الجنس ، ضغط الدم ، السكر ، وجود أمراض قلبية ، التدخين ، الكحول ، التمارين الرياضية عند المرضى و الشهود . كما قمنا بإجراء تحاليل مخبرية و ECG و أيكو قلب و CT دماغ أو MRI دماغ . النتائج: لوحظ زيادة الاحتشاءات الفجوية عند المرضى الذين لديهم ارتفاع توتر شرياني (P-value=0.0001) و (OR=9.9) ، المدخنين (P-value=0.002) و (OR=5.2) ، ومرضى الداء السكري (P-value=0.001) و (OR=5.3) ، بينما كان هناك نقص في حدوث الاحتشاءات الفجوية لدى الرياضيين (0.002P-value=) و (OR=2.6) . لم يكن هناك خطر لحدوث الاحتشاءات الفجوية عند المرض الذين لديهم أمراض قلبية (P-value=0.6) و (OR=0.8) ، فرط كولسترول الدم (P-value=1) و (OR=1)، الكحوليين (P-value=0.7) و (OR=0.8) . الاستنتاج : المرضى الذين لديهم فرط توتر شرياني أو داء سكري أو المدخنين أو الذين ليس لديهم أمراض قلبية يملكون خطر عالٍ للاحتشاءات الفجوية ، بينما الذين يمارسون التمارين الرياضية بشكل مستمر هم أقل خطر لحدوث الاحتشاءات الفجوية . Purpose: Lacunar infarcts is an important stroke subgroup with unique clinical and pathologic features, but risk factors for lacunar infarcts have been rarely documented. To address this matter, we studied 65 patients had lacunar infarction at Department of Neurology , Tishreen University Hospital , Lattakia , Syria , and 65 controls during the period between May 2017 – May 2018 . Methods: We obtained information concerning risk factor exposure status among the patients by a structured questionnaire , we recorded age , sex , blood pressure , glucose , heart diseases , cigarette smoking , alcohol drinking , physical exercise for patiens and controls .We do laboratory tests and ECG and echocardiography and CT brain or MRI . Results: Significantly increasing the risk of lacunar stroke were hypertension (P-value=0.0001) and (OR=9.9), Current smokers (P-value=0.002) and (OR=5.2), diabetes (P-value=0.001) and (OR=5.3) , whereas frequent physical exercise was associated with a significantly decreased risk )P-value= (0.002and (OR=2.6). There was no risk of lacunar stroke associated with heart disease (P-value=0.6) (OR=0.8) , high cholesterol (P-value=1) and (OR=1) , alcohol drinking (P-value=0.7) and (OR=0.8). Conclusions: Patients with hypertension or diabetes, current smokers, those who have not heart disease, are at a higher risk of lacunar stroke, whereas those who undertake regular physical exercise may be at lower risk.